In vivo angiogenesis in tissues penetrating into porous β-tricalcium phosphate scaffolds. Issue 72 (19th July 2016) - Ma, Chao; Wang, Zhen; Lu, Xiao; Lu, Jian-Xi; Bai, Feng; Wang, Chao-Feng; Li, Li; Hou, Shu-Xun; Wang, Hua-Dong
Abstract : In vivo angiogenesis in a three-dimensional bone graft after the implantation of spherical porous β-tricalcium phosphate scaffolding materials into lumbodorsal fascia of New Zealand rabbits. Abstract : In order to understand in vivo angiogenesis in a three-dimensional bone graft and the surrounding tissue penetration into the scaffolds, we implanted spherical porous β-tricalcium phosphate (β-TCP) scaffolding materials into the lumbodorsal fascia of New Zealand rabbits. At different times postoperatively, non-decalcified tissue sections were prepared and analyzed. Results showed that obvious angiogenesis accompanied the surrounding tissue penetration towards the center of implanted porous sphere. Quantitative analysis revealed that during the angiogenetic process there was a rapid increase in vessel numbers in the first 4 weeks but a significant drop afterwards, and there was a steady growth for vessel remolding (diameter expanding) after implantation. Further analysis on the distribution of vessels with different calibers indicated that small capillaries (50 μm or less in diameter) and arterioles (50–100 μm in diameter) accounted for the most part (>93.3%) while the proportion of large vessels (>100 μm in diameter) increased to 6.66% on the 12 th week after implantation. In addition, we adopted a stereological method to compare angiogenesis and tissue penetration in the biomaterial implants quantitatively. With the scaffolds grafted, material biodegradation became evident in the outermost zone and was in close correlation with the increased blood vessel volume. To sum up, angiogenesis was a prerequisite for tissue penetration into the scaffolds, a process influenced by blood vessel formation and material biodegradation.